Together, right now - Fadeeva, Olʹga (Olga Alekseevna) (Blue Dot Kids Press, 2026)
"Right now you are here ... reading this book. Now imagine what someone else is doing at this exact moment two blocks away. What about someone across the country? Or an animal on the other side of our big, beautiful planet? What else is happening round the world, right now?"--book jacket.